Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1054/bjoc.2001.1829
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant high-dose medroxyprogesterone acetate for early breast cancer: 13 years update in a multicentre randomized trial

Abstract: SummaryThe authors updated their report on a randomized trial initiated in 1982 comparing, in early breast cancer, high-dose IM Medroxyprogesterone acetate (HD-MPA) adjuvant hormonotherapy during 6 months with no hormonotherapy; node-positive patients also received 6 courses of IV CMF (day 1, day 8; q.4 weeks). 246 node-negative (NN) and 270 node-positive (NP) patients had been followed for a median duration of 13 years. Previous results were confirmed in this analysis on mature data. In NN patients, relapse-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The success of these regimens fostered the assumption that progesterone would similarly counteract the proliferative effects of estrogen in breast cancers. Indeed, in the absence of chemotherapy, high-dose MPA increases disease-free and overall survival in node-negative premenopausal patients (39). However, the same study found that MPA therapy led to worse outcomes for node-positive premenopausal patients, suggesting that the success of MPA therapy in breast cancer is context dependent.…”
Section: Discussionmentioning
confidence: 96%
“…The success of these regimens fostered the assumption that progesterone would similarly counteract the proliferative effects of estrogen in breast cancers. Indeed, in the absence of chemotherapy, high-dose MPA increases disease-free and overall survival in node-negative premenopausal patients (39). However, the same study found that MPA therapy led to worse outcomes for node-positive premenopausal patients, suggesting that the success of MPA therapy in breast cancer is context dependent.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, in agreement with the results presented here, the role of Pg in the induction of apoptosis via induction of NOSII to increase NO levels was shown in ovarian cancer cells, 30 indicating a general function of Pg in this mechanism. In fact, several randomised studies and clinical trials have shown that treatment with progestogens led to significant though modest improvement of the relapse-free survival, 42,43 and that inclusion of progestogens in hormone replacement therapy reduces the risk of recurrence, which is associated with an increase in the apoptosis/proliferation ratio within the tumour. 44 The balance between cell death and cell proliferation determines tumour growth rate and even a small alteration in these parameters can be important for the expansion or regression of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, two of the older trials that used long-term MPA dosing reported 12-and 13-year follow-up data, and a retrospective subset analysis suggested a benefit in post-menopausal patients. A total of 950 patients were randomized to chemotherapy with or without a six-month course of MPA, given in a one-month induction, five-month maintenance protocol [14, 15]. In both trials, the MPA-treated subsets of patients had improved disease-free survival ( P = 0.01 in one trial; in the other, P = 0.06 for node-negative and P = 0.002 for node-positive patients).…”
Section: Identification and Validation Of Medroxyprogesterone Acetatementioning
confidence: 99%
“…Estrogen combined with MPA was demonstrated to be deleterious in the form of HRT, so it is reasonable that MPA should not be administered to patients that are pre-menopausal. Intriguingly, patient responses were not well-correlated with progesterone receptor expression [14, 16, 17], which suggested that more recent data showing that interaction of MPA with the GR may be relevant.…”
Section: Identification and Validation Of Medroxyprogesterone Acetatementioning
confidence: 99%